IDENTIFIKASI PERLINDUNGAN ARSIP STATIS TERHADAP BENCANA KEBAKARAN: STUDI KASUS DI ARSIP NASIONAL REPUBLIK INDONESIA - Anggita Wigati, Fiqriena; Aulia Rachman, Margareta (BACA: Jurnal Dokumentasi dan Informasi, 2019)
This study discusses the protection of static archives against fire disasters in the ANRI. Static archive protection is needed because the static archive has historical and national values. Moreover, the archive collection owned by ANRI is approximately 13,232 conventional archives and 8,080 new media archives. If the archive owned by ANRI is lost due to a disaster, the loss is not only felt by the institution but by the Indonesian. Not only archives that must be considered but the building or building where the archive is stored also needs attention. Buildings must be designed to store and protect archives from disasters. One of the disasters that caused many losses both soul and material was fire. For this reason, this study aims to identify the protection of static records against fire disasters at the National Archives of the Republic of Indonesia, especially in the Directorate of Preservation. This study uses a qualitative approach to the case study method. Data collection methods used are observation and interview. The 11 informants were selected using purposive sampling method, with criteria of staff who formulated, implemented and fostered the field of preservation at ANRI. Static archive protection against fire disasters in ANRI cannot be considered as a small disaster risk because it will cause loss in the static archive collection that is owned. Protection is needed through the stages of prevention, preparation, reaction and recovery. Routine checks must be carried out on tools, training regularly, and special teams are made with clear job descriptions in case of a fire disaster.